Advances in group processes. Vol. 34 - Thye, Shane R.; Lawler, Edward J. (Advances in group processes ;, 2017)
Advances in Group Processes publishes theoretical analyses, reviews and theory-based empirical chapters on group phenomena. The series adopts a broad conception of ́œgroup processes.́ This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, trust, justice, social influence, identity, decision-making, intergroup relations and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, economics, business, philosophy, mathematics and organizational behavior. Volume 34 brings together papers that address theoretical and empirical issues related to the spread of status value, reward expectations theory, age and gender effects, and measuring the impact of status manipulations. Other contributions examine cognitive orientation, perspective taking and empathy, the stability of values, and group perceptions during computer-mediated communication. Overall, the volume includes papers that reflect a wide range of theoretical approaches from leading scholars who work in group processes.